Women and Rainfall: An Eco-ritual Among the Alps of the Past - Bassi, Dario (Matrix, 2025)
This paper focuses on a 'legendary' ritual that took place in the 19th century near the church of San Salvatore in Albosaggia, a small village in Valtellina, an Alpine valley in northern Italy. The rite in question comprised the immersion of human skulls in order to attract and repel rainwater according to the needs of the moment. The ritual is analyzed through the recovery and problematization of a heterogeneous corpus of sources attesting to its historicity. A hypothesis is then proposed on the connections between water, the dead and the feminine that underpin them. Thus, the study proposes the adoption of the term 'eco-ritual' to encapsulate this phenomenon. In doing so, a culturally distinctive form of female agency is displayed: the symbolic power to influence the water cycle, which is at the same time an ontological and economic vivifying force.